Estudo da utilização de realidade aumentada no ensino técnico - Silva, Roney Pereira da (Brasil, 2024)
Over the years, Augmented Reality (AR) has gained applications in several areas, one of these areas was the area of education, which used the tool as a means of developing more dynamic classes, making the theoretical content taught in the classroom more interesting. In general, technical courses still do not have in their curriculum the use of augmented reality as a support in the teaching of disciplines in the technical area, so that when the student does not have access to the practical class due to the unavailability of adequate equipment, it ends up being restricted. to the theoretical content of the equipment. In this way, this work develops an academic research that encourages the use of augmented reality as a technological support tool, but also prepares students with a certain practice through augmented reality. As a result, a portfolio of parts from the Organic Elements of Machines discipline of the Technical Course in Electromechanics at IFAM was developed, which was applied through a mini-course to the students of the course.